Les débuts professionnels des auteurs et des autrices de bande dessinée - Sylvain Aquatias; Alain François (Images du Travail, Travail des Images)
The study of the trajectories of comic book authors born between 1980 and 1999 and residing in Charente shows that their professionalization isn’t an easy one. On the one hand, they are forced to resort to multiple activities: activities unrelated to comics, activities quite similar (storyboarding, illustration, graphic communication, animation, etc.) or less similar (teaching and educational activities, sale in bookstores, etc.). On the other hand, work opportunities follow the development of networks: student networks, local professional networks and extended networks which will also define the advancement of careers. Networks also define social support in the face of the uncertainty of professional success. Finally, there is an intermediate level, linked to integration into local professional relations which also allows strong links. Above all, networks transform activities and these act in return on the networks. This is how the trajectories are structured, with the resources of a rich local environment.